NON-FINANCIAL COMPANIES: EARNINGS MANAGEMENT AND THE FACTORS THAT INFLUENCED - Nigel Hans Winarta; Magda Siahaan; Theonino David Nauli (Transpublika Publisher, 2024)
This research examines how various factors such as independent commissioners, audit committees, institutional ownership, firm size, leverage, firm age, and audit quality impact earnings management. Data for this study was collected from 94 non-financial companies listed on the Indonesia Stock Exchange between 2017 and 2019, totaling 278 data points. Purposive sampling was used to gather sample data for analysis. The findings of the study indicated that company age and audit quality have a significant influence on earnings management, whereas independent commissioners, audit committees, audit committee independence, institutional ownership, company size, and leverage do not affect earnings management.